Modelagem e simulação de uma destilaria autônoma de produção de etanol de primeira geração (E1G) - Fonseca, Gabriel de Castro (Universidade Federal de São Carlos, 2014)
Most of the operations in an autonomous distillery for production of ethanol are carried on in a continuous fashion. The fermentation stage, however, may be projected to work either continously or semicontinuously. The steady-sate continuous operation (after the start-up) may be easily coupled to other unit operations of the process. On the other hand, in the semicountinuous operation, each fermentation vat operates in unsteady state, thus it is necessary to design a set of vats that enables the coupling between the fermentation and the process, which may be challenging. This study intended to implement mathematical models in EMSO process simulator of both industrial configurations of the fermentation process: a system of six parallel fed-batch bioreactors and a system of four continuous steady-state bioreactors in series. The process was modeled at macroscopic level based on the material balances for cells, substrate and product. Kinectic models accounting for product and substrate inhibition were used. Both configurations were added to a previously built model of a complete autonomous distillery in which the fermentation stage was represented by a stoichiometric conversion model. In the fed-batch process, due to the solution of mass and energy balances in the fermenters, it was possible to observe the temporal evolution of variables such as the concentrations of yeast, sugar and ethanol in their interiors, the volume of solution in each fermenter and the rate of heat removal needed in order to keep the fermenters temperatures constant. The simulated autonomous distillery processes 500 t/h of cane with varying levels of sucrose. For a content of 13% sucrose, 338.0 t/h of centrifugated wine were obtained in the continuous operation, containing 8.3% by weight of ethanol, which resulted in the production of 30.1 t/h of hydrate ethanol containing 93.5% ethyl alcohol in weight. In fed-batch operation, 417.5 t/h of centrifugated wine (6.3% ethanol by weight), which resulted in 27.9 t/h of hydrous ethanol (93.5% by mass). In both configurations, simulations were performed to evaluate the influence of the sucrose content in the process input (11 to 15% by weight of sucrose) over the process response. The results of these simulations were compared to those obtained for the model of stoichiometric conversion under the same conditions. Regarding the three evaluated configurations for the fermentation stage, it was observed that the model of stoichiometric conversion can be properly employed in the simulations, being mostly suitable for optimization studies of the autonomous distillery with semicontinuous operation due to its fast convergence. However, it is worth mentioning that the inhibitory effects are not reproduced in the fermentation step for this model, thus preliminary studies should be performed using the mathematical model implemented in continuous or discontinuous configuration.
Keywords: Fermentação; Etanol; Modelagem computacional e simulação; Bioprocesso; Biorrefinarias; Simulação de processos; Fermentation; Process simulation; Bioprocess; Biorrefinary; ENGENHARIAS::ENGENHARIA QUIMICA